Adequacy of the Fogging Test in the Detection of Clinically Significant Hyperopia in School-Aged Children - João Esteves Leandro; Jorge Meira; Carla Sofia Ferreira; Renato Santos-Silva; Paulo Freitas-Costa; Augusto Magalhães; Jorge Breda; Fernando Falcão-Reis (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of the “fogging test,” performed with a +2 diopters (D) lens, in the exclusion of clinically significant hyperopia in school-aged children. Methods. We studied 54 children between 5 and 11 years of age, with 10/10 best-corrected bilateral visual acuity (VA) without significant degree of correction. VA was assessed in each eye with a “bilateral” +2 D sphere over-refraction followed by cycloplegic retinoscopy. The capacity of the test to detect hyperopia of ≥+2 D and ≥+1.5 D was evaluated by examining the respective receiver operating characteristic (ROC) curves and sensitivity and specificity values for different cutoff values of VA. Results. For the detection of hyperopia ≥+2 D, the area under the ROC curve (AUC) was 0.955 (p≤0.001). The VA cutoff with best discriminative capacity was ≥5/10, with a sensitivity of 100%, specificity of 79%, positive predictive value (PPV) of 57%, and negative predictive value (NPV) of 100%. In respect of ≥+1.5 D hyperopia, the test capacity was lower (AUC = 0.832; p≤0.001). The best VA cutoff was also of ≥5/10, with a PPV of 81% and a NPV of 85%. Conclusion. The accuracy of the test was high for the evaluation of ≥+2 D hyperopia but lower for ≥+1.5 D hyperopia. For the detection of ≥+2 D hyperopia, the VA cutoff of <5/10 may permit the exclusion of clinically significant hyperopia in selected children, without the need for cycloplegia. For the same cutoff, the PPV was low, meaning that in children with ≥5/10 VA cycloplegic refraction remains obligatory.